Self-sustainability through renewable energy production in mali : zero-energy-houses - Bakary Konare (My University, 2019)
Enerji endüstrisi, ekonomik ve sosyal meslek perspektiflerinden, ürün, hizmet ve malsağlayıcılarından en önemli alanlardan biridir. Bu endüstri, daha iyi yaşam koşullarınınsağlanması için tüm insan faaliyetlerine önemli ölçüde katkıda bulunduğu için, nüfusunve ulusal ekonominin ihtiyaçlarından ayrılamaz. Pozitif değerleriyle birlikte, enerjiendüstrisi, dünyada sürdürülebilirliğe karşı gözlemlenen bazı zararlı taraflara sahiptir.Günümüzde, konvansiyonel enerji tüketimi, dikkatsiz uygulamalar, evrenimizi korkunçbir hedefe götürüyor. Konut sektörü, geleneksel yakacak odun yakma yoluyla karbonemisyonlarından sorumlu ana sektörlerden biridir. Bu çalışma, insanların, yenilenebilirenerji kaynaklarını yerinde kullanacak olan sıfır enerji evi kavramının uygulanmasıyoluyla Mali'deki aktif prosumerlere tüketicilerin geleneksel pasif statüsünden nasılçıkabileceğini açıklamaktadır. Bu hibrid sistem, yenilenebilir teknolojiler vasıtasıylayıllık bazda ev sakinlerine elektrik ve iç mekan rahatlığı sağlayacaktır. Bu amaçla, herteknoloji için matematiksel model geliştirdik ve MATLAB Simulink kullanarak simüleettik. Hava Durumu verileri, sistemin Mali'de uygulanabilirliğini kanıtlamak için Pvwattprogramı kullanılarak deneysel olarak değerlendirildi. Daha sonra üç teknolojiyi iki farklıyapıya entegre ettik; biri saman balya ve diğeri ahşap keresteden yapılmıştır. Bireyselinşaat ve enerji verimliliği yapılan toplam maliyet karşılaştırıldıktan sonra, saman balyainşaat consensually seçmek için en iyi alternatif oldu.

As engine is essential for vehicles, electricity is seen to be the essence for industries,technological development, and economic growth. The force multiplier enables humanbeings to convert raw materials into tangible and intangible products or services. Theindustry of energy is one of the most significant area from the perspectives of economicand social vocation, as provider of products, services and commodities. This industry isinseparable from the needs of the population and the national economy, as its servicescontribute significantly to all human activities for the achievement of better livingconditions. In spite of its positive sides, energy industry has some detrimental effects tothe sustainability in the world. Nowadays, conventional energy and natural resourcesoverconsumption, careless practices, is leading our universe to dreadful destination.Residential sector is one of the main responsible for carbon emissions through traditionalfirewood burning. This study describes how people can quit their traditional passive statusof consumers to active prosumers ‘’Prosumption’’ in Mali through implementation ofzero-energy house concept, which will harness renewable energy sources on site. Thishybrid system will provide electricity and indoor comfortability to the house occupantson yearly basis by the means of renewable technologies. For this purpose, we developedmathematical model for each technology and simulated them by using Matlab Simulink.Weather data were experimentally evaluated using Pvwatt program to prove theapplicability of the system in Mali. Then we integrated the three technologies into twodifferent construction; one with straw-bales and the other made of wooden timber. Aftercomparison of the total cost incurred in individual construction and energy efficiency,Straw bales construction was consensually the best alternative to choose.
Keywords: Endüstri mühendisliği; Hibrid sistem; Industrial engineering; Matlab simulink; Overconsumption; prosumerler; Prosumption; Renewabletechnologies; Saman balya; Straw-bales; Sustainability; sürdürlebilirlik Hybrid; Yenilenebilir teknolojiler